Measuring The Service Quality Of Selangor Area Farmers’ Organisations - Abd. Halid, Mohammed Rizal (2007)

(untitled)
Agriculture sector is the third engine of growth for the Malaysian economy. The government has recognized agriculture sector as a valuable prospect that must be explored. Within the Ministry of Agriculture and Agro-based Industry, the agriculture sector has been restructured in particular to improve its service quality. The objective of this study is to examine the effectiveness of the services provided by the Selangor Area Farmers’ Organisations (AFOs) under the Farmers Organisation Authority (FOA) of the Ministry of Agriculture and Agro-based Industry to their members Farmers, under the Farmers’ Organisations of the FOA have certain expectations about the services they received. These expectations are beliefs about the upcoming services, which when compared with the perceived actual service delivered will influence the level of satisfaction of farmers and the judgment of AFOs and FOA’s overall service quality. The most popular measure of service quality, the SERVQUAL was used in this study to evaluate the quality of service provided in terms of what farmers expect and what they actually received. The SERVQUAL consists of five dimensions of service quality namely tangibles, reliability, responsiveness, assurance and empathy. A pair of 22-item likert scale questions were used in this study to measure the levels of expectation and perception of farmers. An analysis covering 104 farmers of Selangor area farmers’ associations were selected as respondents. Frequency counts and percentages were used to analyse the demographic traits of the respondents. Gap Analysis was used to identify the differences between farmers’ expectations and perceptions. Factor analysis was used to determine the underlying patterns of the statements made in the 22-items of the SERVQUAL instrument and a logistic regression analysis was conducted to further examine the relationship among those underlying patterns. This study revealed that there was an overall service quality gap between expectations and perceptions of -0.6306. The responsiveness dimension represented the lowest score (-0.6899) on the SERVQUAL scale, followed by tangibles (-0.6779), reliability (-0.6500), assurance (-0.5697) and empathy (-0.5654). Results of the factor analysis show that three factors had eigenvalue greater than 1.0. These three factors were work ethics (11.812), customer care (1.036) and appearance (1.008). Results of the logistic regression analysis show the odds ratio of those three factors reveals that when holding all other independent variables constant, for each one-point increase on the five-point work ethics, customer care and appearance scale, there is a 7.880, 7.909 and 6.382 times more likely that members of the Selangor Area Farmers’ Organisation will be satisfied with the quality of services provided respectively. Results from the gap analysis can provide important information for the FOA to plan and develop more programs for improving the quality of services delivered by the FO’s to the farmers. With such programs, it would help to improve service quality of AFOs so that the gap between expectations and perceptions among the farmers can be narrowed. Meanwhile, results obtained in the factor analysis and logistic regression provided an extra data and information to the Area Farmers’ Organisations in Selangor by revealing the unseen factors that could be useful to them. The analysis founded that, factors such as work ethics, customer care and appearance are significant to service quality. FOA should applied these factors as an indicator to enhance the service quality.